1996
DOI: 10.1021/ac951207r
|View full text |Cite
|
Sign up to set email alerts
|

Bioluminescent Assay for Heroin and Its Metabolites

Abstract: Illicit heroin is trafficked as a solid particulate drug, while heroin abuse is monitored by testing urine samples for its principal metabolites, morphine and morphine-3-glucuronide. Two novel bacterial enzymes were used in the development of a linked-enzyme assay for heroin and its metabolites: heroin esterase, which converts heroin to morphine, and morphine dehydrogenase, which oxidizes morphine to morphinone with the concomitant reduction of NADP+. A bioluminescent assay involving heroin esterase, morphine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…The HerE enzyme is the first structure reported of an esterase known to hydrolyze heroin. Hence, the structure provides a framework for improving the specificity and sensitivity of a recently reported heroin biosensor (2). The high bimolecular rate constant for phenyl acetate (approximately 1000-fold higher than 6-acetylmorphine) implies that with engineering of the active site, the specificity constant for heroin could be substantially improved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HerE enzyme is the first structure reported of an esterase known to hydrolyze heroin. Hence, the structure provides a framework for improving the specificity and sensitivity of a recently reported heroin biosensor (2). The high bimolecular rate constant for phenyl acetate (approximately 1000-fold higher than 6-acetylmorphine) implies that with engineering of the active site, the specificity constant for heroin could be substantially improved.…”
Section: Discussionmentioning
confidence: 99%
“…1A) (2). The higher activity (k cat K m Ϫ1 ) of HerE toward smaller substrates such as phenyl acetate (Fig.…”
mentioning
confidence: 92%
“…Finally, the discovery of this soluble cocaine esterase is of particular interest for its use in a potential illicit-drug sensor. Enzymatic detection of illicit heroin has already been described (12). In conjunction with a suitable NADP ϩ -dependent dehydrogenase active against ecgonine methyl ester, the cocaine esterase could enable simultaneous detection of heroin and cocaine, using established bioluminescence technology (12).…”
Section: Vol 66 2000mentioning
confidence: 99%
“…We envisaged that the isolation of microorganisms from the environment capable of metabolizing drugs, such as cocaine and heroin, as carbon sources for growth might provide a good source of enzymes which could be utilized as recognition components in biosensors for the detection of illicit drugs. Previous work in our laboratory has shown that the enzymes initiating heroin metabolism in bacteria could be successfully used in conjunction with bacterial luciferase for the detection of nanogram quantities of heroin (5,12,24). Work has subsequently been directed towards identifying appropriate enzymes active against cocaine.…”
mentioning
confidence: 99%
“…The first steps in the transformation of morphine and codeine are oxidation of the 6-hydroxyl group to a ketone by a NADP +dependent morphine dehydrogenase (MDH) to give morphinone and codeinone ( Figure 1) [1][2][3], and saturation of the 7,8-double bond by an NADH-dependent morphinone reductase to give hydromorphone and hydrocodone [4][5][6]. Oxidation of morphine by MDH was made the basis of a rapid and highly sensitive assay for opiates in urine [7,8], and the combined MDH-morphinone…”
Section: Introductionmentioning
confidence: 99%